Association of some psychosocial factors with anthropometric measures in nationally representative sample of Iranian adolescents: the CASPIAN-III study. Issue 1 (December 2015) - Baygi, Fereshteh; Kelishadi, Roya; Qorbani, Mostafa; Mohammadi, Fatemeh; Motlagh, Mohammad; Ardalan, Gelayol; Mansourian, Morteza; Arzaghi, Seyed; Asayesh, Hamid; Heshmat, Ramin
Abstract Background During the last two decades, adolescent obesity has increased in western countries. In Iran-as a developing country- the prevalence of obesity is raised among youngsters as well. This study conducted to identify an association of adolescents' loneliness, self-confidence and relationship with others in home and school environment with their weight status. Methods In this cross-sectional national survey, 5682 students aged 10–18 years from urban and rural districts of 27 provinces of Iran were selected via stratified multi-stage sampling method. Data on psychological problems of students was gathered through a questionnaire. Height, weight, and waist circumferences were measured according to standard protocols. Body mass index (BMI) and waist- to-height ratio was calculated. Results Boys which did not have best friends, spend time with their friends after school or get acceptance from them, had higher BMI than others. Only girls who did not spend time with their friends had higher BMI (19.48 ± 4.28) vs. (19.09 ± 3.92) and WC (71.04 ± 21.29) vs. (69.15 ± 17.43) than others, P  < 0.05. In both sexes, adolescents who had sense of pressure about doing homework or had difficulties in relationship with their parents had higher BMI and WC values. Girls who reported being victim of violent behaviors (being bullied), had lower BMI compared to others. Risk of being overweight and obese, but not abdominal obese was statistically higher in adolescents not having close friends (OR = 1.81, CI: 1.11–2.95). Lack of self-confidence increased only the risk of obesity in teens (OR = 1033, CI: 1.09–1.64). Conclusions Our findings suggest that strategies for prevention of overweight and obesity in adolescent should be taking into account a deeper knowledge of psychosocial issues due to be able to design more effective programs for treating overweight teens.